A taxonomic revision of the Sinopterus complex (Pterosauria, Tapejaridae) from the Early Cretaceous Jehol Biota, with the new genus Huaxiadraco - Pêgas,Rodrigo V.; Zhou,Xuanyu; Jin,Xingsheng; Wang,Kai; Ma,Waisum (PeerJ, 2023)
Tapejarids are edentulous pterosaurs particularly abundant in the Chinese Jiufotang Formation, counting with over 10 described specimens and dozens of undescribed ones. A total of seven nominal tapejarid species (within two genera) have been proposed, though it is disputed how many of those are valid instead of sexual or ontogenetic morphs of fewer, or a single, species. However, detailed revisions of the matter are still lacking. In the present work, we provide a specimen-level survey of anatomical variation in previously described Jiufotang tapejarid specimens, as well as of six new ones. We present qualitative and morphometric comparisons, aiming to provide a basis for a taxonomic reappraisal of the complex. Our results lead us to interpret two Jiufotang tapejarid species as valid: Sinopterus dongi and Huaxiadraco corollatus (gen. et comb. nov.). Our primary taxonomic decisions did not rely around cranial crest features, which have typically been regarded as diagnostic for most of these proposed species albeit ever-growing evidence that these structures are highly variable in pterosaurs, due to ontogeny and sexual dimorphism. However, a reassessment of premaxillary crest variation in the Sinopterus complex reveals that while much of the observed variation (crest presence and size) can easily be attributed to intraspecific (ontogenetic and sexual) variation, some of it (crest shape) does seem to represent interspecific variation indeed. A phylogenetic analysis including the species regarded as valid was also performed.
Keywords: Taxonomy; Pterosaur; Linear morphometrics; Ontogeny; Allometry; Phylogeny; Jiufotang Formation; Osteology